Utilization of Interactive Digital Platforms in PAI Learning to Improve Religious Literacy of Elementary School Students - Cita Suci Soleha; U Abdullah Mu’min; Mahamadaree Waen; Shifa Aulia Firnanda; Ahmad Ripa'i (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to explore the use of interactive digital platforms in Islamic Religious Education (PAI) learning in primary schools and their impact on improving students ' religious literacy. This study used a qualitative approach, where data were collected through in-depth interview techniques, direct observation, and collection of relevant documents. Based on the results of the study, the use of interactive digital platforms plays an important role in encouraging increased motivation and involvement of students during the learning process. The effectiveness of the use of this technology can be seen from the increase in the average academic score of students, which was originally at 70 and increased to 85 after digital innovation was applied in learning activities. Students demonstrate better social and collaborative skills, as well as being able to understand and apply religious teachings in the context of everyday life. The positive response from teachers and parents to the implementation of digital platforms also reflects the need for collaboration between educators and parents in creating an optimal learning environment. This study concludes that the use of technology in PAI education not only improves learning outcomes, but also strengthens the character of students based on religious values. Recommendations were given to improve teacher training and investment in technological infrastructure to facilitate more effective implementation in the future.